Challenges in Implementing the Independent Curriculum in English Language Learning at MA Palapa Nusantara, East Lombok - Wardani, Khairul; Usuluddin, Usuluddin; Arfah, Hajriana; Prasetyaningrum, Ari (Journal of English Language and Education, 2025)
This study aims to identify the challenges faced by teachers in implementing the Independent Curriculum in English learning and to explore strategies that enhance student engagement. Using a qualitative approach with observation, interviews, and questionnaires, the research involved three English teachers and three high-achieving students at MA Palapa Nusantara, East Lombok. The findings reveal that teachers encounter limited resources, insufficient training, and difficulties in adapting teaching methods to diverse student needs. Students, meanwhile, struggle with motivation, limited practice, and adapting to independent learning styles. Effective strategies identified include the use of technology, project-based activities, and communicative approaches. This study highlights the gap between curriculum principles and classroom realities, offering insights for improving English language learning in Indonesia.